Antibacterial activity of methanolic and acetone extract of some medicinal plants used in indian folklore - J. P. Patel,; Bharat Gami,; Kanti Patel,; Raksha Solanki, (International Journal of Phytomedicine, 2011)
Antibacterial study of methanolic and acetone extract in crude and treated (with 50 % lead acetate) form of medicinal plants Alstonia scholaris Linn. R.Br. (Stem bark, Apocynaceae), Achyranthus aspera Linn. (Whole plant, acantheceae), Moringa oleifera Lam. (Leaves, Morinaceae), Tinospora cordifolia (Stem, Menispermaceae), and Enicostema hyssopifolium (Willd) (Stem, Gentianaceae). Extractive values in methanol were found higher then the extractive value in acetone, for all plants. All extract of plants were tried at 40-mg/ml concentrations against eight strains of bacteria, by agarwell-difusion test. Acetone extract was found more active as compared to methanol extract. Phytochemical investigation revealed crude and treated extracts of all plants were containing more or less same type of chemical constituents (except protein and carbohydrate). Selected eight strains of bacteria were study for antibiotic susceptibility against standard antibiotics like Ampicillin (10µg), Tetracycline (25µg), Gentamicin (30µg), Co-Trimoxazole (25µg), Amikacin (10µg), by Octadisc. Treated extract of M. oleifera and A. scholaris were count as to new source of antimicrobial agent for the infectious diseases (Typhoid).